Some Observations Regarding to the Implementation of the Private School Act, B.E. 2550 And the Regulation of the Ministry of Education Pertaining to Work Protection for Private School Principals and Teachers, B.E. 2542: in Case of Benefits - สมทรัพย์, ชุติพงศ์ (Ganesha Journal, 2019)
The Private School Act, B.E. 2550 and the Regulation of the Ministry of Education Pertaining to Work Protection for Private School Principals and Teachers, B.E. 2542 stipulates that teachers must receive compensations and benefits not less than what the labor law has designated. Some observations regarding the implementation of the said laws and regulations in case of benefits witness the lack of the specific definition of “benefits” which caused problems within the interpretation of the law. It affected the use of the law correctly and fairly, the deficiencies in the provisions of the principle of calculating teaching per diem as compared to the minimum daily wage, regarding the endless over-time work on week-days, the payment principle for weekend over-time work that was not consistent with holiday payment, the recompense for exceeding 20 years of work which should be covered by the labour protection law, and the possibility to directly file a lawsuit without going through the work protection committee.